2021
DOI: 10.1093/plphys/kiab090
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal morphology and physiology explain varied sensitivity to abscisic acid across vascular plant lineages

Abstract: Abscisic acid (ABA) can induce rapid stomatal closure in seed plants, but the action of this hormone on the stomata of fern and lycophyte species remains equivocal. Here, ABA-induced stomatal closure, signaling components, guard cell K+ and Ca2+ fluxes, vacuolar and actin cytoskeleton dynamics, and the permeability coefficient of guard cell protoplasts (Pf) were analyzed in species spanning the diversity of vascular land plants including 11 seed plants, 6 ferns and one lycophyte. We found that all 11 seed plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 66 publications
8
28
0
Order By: Relevance
“…On the other side, evidence suggests that hydraulic and osmotic mechanisms independent of ABA are the major drivers of stomatal closure in ferns (Brodribb & McAdam, 2011; Cardoso & McAdam, 2019; Cardoso et al, 2019; McAdam & Brodribb, 2012a, 2012b). Indeed, it was recently shown that ferns and lycophyte species lack ABA‐responsiveness but an osmotic‐mediated stomatal closure mechanism is likely found in these species (Gong et al, 2021). However, this study was performed using an extremely high concentration of sorbitol (800 mM).…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, evidence suggests that hydraulic and osmotic mechanisms independent of ABA are the major drivers of stomatal closure in ferns (Brodribb & McAdam, 2011; Cardoso & McAdam, 2019; Cardoso et al, 2019; McAdam & Brodribb, 2012a, 2012b). Indeed, it was recently shown that ferns and lycophyte species lack ABA‐responsiveness but an osmotic‐mediated stomatal closure mechanism is likely found in these species (Gong et al, 2021). However, this study was performed using an extremely high concentration of sorbitol (800 mM).…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with previous findings of a lack of stomatal closure response to endogenous ABA levels in ferns [28,29], and the lack of stomatal phenotype for ABA-insensitive mutants of the C. richardii OST1 ortholog GAIA1 [31] in sharp contrast to the wilty phenotypes of angiosperm ABA biosynthesis and signalling mutants [49,[62][63][64]. In addition, a recent study showed a lack of ABAmediated K + efflux from the guard cells of fern and lycophyte species, further emphasising differences between the stomatal responses of seed plants and other vascular plant groups [65]. Together, these results support a passive model for stomatal closure in ferns [29], whereby guard cell turgor is dependent on leaf turgor rather than ABA-dependent activation of guard cell-expressed ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the stomatal pore aperture is a major factor in determining plant productivity and drought tolerance [ 11 , 12 , 13 , 14 , 15 ]. GABA-induced stomatal control has gained particular attention in recent years.…”
Section: Introductionmentioning
confidence: 99%